The UN Commission on Life Saving Commodities 3 years on: global progress update and results of a multicountry assessment. Issue 4 (April 2016) - Pronyk, Paul M; Nemser, Bennett; Maliqi, Blerta; Springstubb, Nora; Sera, Diana; Karimov, Rouslan; Katwan, Elizabeth; Walter, Benedicte; Bijleveld, Pascal; ,; ,; ,
Summary: Background: In September, 2012, the UN Commission on Life Saving Commodities (UNCoLSC) outlined a plan to expand availability and access to 13 life saving commodities. We profile global and country progress against these recommendations between 2012 and 2015. Methods: For 12 countries in sub-Saharan Africa that were off-track to achieve the Millennium Development Goals for maternal and child survival, we reviewed key documents and reference data, and conducted interviews with ministry staff and partners to assess the status of the UNCoLSC recommendations. The RMNCH fund provided short-term catalytic financing to support country plans to advance the commodity agenda, with activities coded by UNCoLSC recommendation. Our network of technical resource teams identified, addressed, and monitored progress against cross-cutting commodity-related challenges that needed coordinated global action. Findings: In 2014 and 2015, child and maternal health commodities had fewer bottlenecks than reproductive and neonatal commodities. Common bottlenecks included regulatory challenges (ten of 12 countries); poor quality assurance (11 of 12 countries); insufficient staff training (more than half of facilities on average); and weak supply chains systems (11 of 12 countries), with stock-outs of priority commodities in about 40% of facilities on average. The RMNCH fund committed US$175·7 million to 19 countries to support strategies addressing crucial gaps. $68·2 million (39·0%) of the funds supported systems-strengthening interventions with the remainder split across reproductive, maternal, newborn, and child health. Health worker training ($88·6 million, 50·4%), supply chain ($53·3 million, 30·0%), and demand generation ($21·1 million, 12·0%) were the major topics of focus. All priority commodities are now listed in the WHO Essential Medicines List; appropriate price reductions were secured; quality manufacturing was improved; a fast-track registration mechanism for prequalified products was established; and methods were developed for advocacy, quantification, demand generation, supply chain, and provider training. Slower progress was evident around regulatory harmonisation and quality assurance. Interpretation: Much work is needed to achieve full implementation of the UNCoLSC recommendations. Coordinated efforts to secure price reductions beyond the 13 commodities and improve regulatory efficiency, quality, and supply chains are still needed alongside broader dissemination of work products. Funding: Governments of Norway (NORAD) and the UK (DFID).